Sentencing and the legitimacy of trial justice - Henham, Ralph J., 1949- (Milton Park, Abingdon, Oxon : Routledge, 2012)
'This book discusses the under-researched relationship between sentencing and the legitimacy of punishment. It argues that there is an increasing gap between what is perceived as legitimate punishment and the sentencing decisions of the criminal courts. Drawing on a wide variety of empirical research evidence, the book explores how sentencing could be developed within a more socially-inclusive framework for the delivery of trial justice. In the international context, such developments are directly relevant to the future role of the International Criminal Court, especially its ability to deliver more coherent and inclusive trial outcomes that contribute to social reconstruction. Similarly, in the national context, these issues have a vital role to play in helping to re-position trial justice as a credible cornerstone of criminal justice governance where social diversity persists. In so doing the book should help policy-makers in appreciating the likely implications for criminal trials of'mainstreaming' restorative forms of justice. Sentencing and the Legitimacy of Trial Justice firmly ties the issue of legitimacy to the relevant context for delivering'justice'. It suggests a need to develop the tools and methods for achieving this and offers some novel solutions to this complex problem'--Provided by publisher.
Challenging existing paradigms -- Issues of theory and method -- Punishment rationales in a comparative context -- Discretionary power and sentencing -- Procedural justice and due process -- Deconstructing evidence for sentencing -- Access to justice, rights and accountability -- Sentencing and legitimacy in France and Italy -- Punishment and sentencing as governance.
Includes bibliographical references (pages 320-342) and index.
Keywords: Criminal justice, Administration of -- Philosophy; Punishment -- Philosophy; Sentences (Criminal procedure) -- Philosophy